Utilización de la Pluchea carolinensis en la gingivitis crónica edematosa - Guerra Betancourt, Rosa María; Guerra Betancourt, Katherine; Palomino Carmenate, Eloisa; Guerra Miranda, Juan; Rodríguez Nieves, Mabel; Santiesteban Castro, Joaquin Leandro (Correo Científico Médico, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –><!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> Introducción: se ha demostrado la actividad antiinflamatoria, analgésica, antifúngica, vasodilatadora y espasmogénica in vitro de la Pluchea carolinensis. Objetivo: evaluar la efectividad de la tintura de Pluchea carolinensis en el tratamiento de la gingivitis crónica edematosa. Métodos: se estudiaron 124 pacientes con gingivitis crónica, con edades entre los 15 y 18 años del Servicio de Periodoncia de la Clínica Estomatológica Manuel Angulo Farrán, municipio Holguín. Se distribuyeron en dos grupos de forma aleatoria, se realizó a todos el control de los irritantes locales. El grupo control se trató con sulfato de cobre y el experimental con el fitofármaco en estudio. Se evaluaron las características clínicas de la encía y el sangramiento gingival a los 7, 14, 21 y 30 días. Resultados: la placa dentobacteriana se comportó de igual manera para ambos grupos. Se observaron cambios favorables en las encías a partir de los 7 días, la disminución del sangrado fue mayor a los 30 días La resolución de la inflamación (a los 14 y 30 días) mostró resultados significativos a favor del grupo de estudio; en la gingivitis papilar los resultados fueron mejores, aunque en la gingivitis difusa mejoraron con el tiempo. Conclusiones: la aplicación de la tintura de Pluchea carolinensis redujo la acumulación de placa dentobacteriana, el sangramiento gingival y mejoró la respuesta de los tejidos gingivales. Se demostró una mayor efectividad en la gingivitis marginal y papilar. Palabras clave: gingivitis, Pluchea carolinensis, fitofármaco ABSTRACT Introduction: it had demonstrated anti-inflammatory, analgesic, anti-fungal, and spasmogenic vasodilator action of Pluchea carolinensis. Objective: to evaluate the effectiveness of Pluchea carolinensis tincture in the treatment of chronic edematous gingivitis. Methods: one hundred- twenty four patients aged between 15 and 18 years, with chronic gingivitis it studied in the Periodontics Service of Manuel Angulo Farrán Dental Clinic, Holguin municipality. The sample was divided into two groups randomly. The control of local irritants was determined. The control group was treated with copper sulphate and the study one with phytomedicine. The gingiva and gingival bleeding clinical features at 7, 14, 21 and 30 days were assessed. Results: the dental plaque behaved similarly in both groups, showing favorable changes in the gums after seven days, bleeding was reduced after 30 days. Regarding the inflammation, significant results in the study group, at 14 and 30 days were observed. Considering papillary gingivitis better results were showed, although diffuse gingivitis improved over time. Conclusions: the use of Pluchea carolinensis tincture reduced the accumulation of plaque, gingival bleeding and improved gingival tissue response, which proved more effectivess in marginal and papillary gingivitis. Key words: gingivitis, Pluchea carolinensis, phytomedicine <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>